Contextualizing Acid–Base Chemistry Learning through Local Wisdom: Development of an Interactive E-Module Based on the Poto Wua Ta’a Tradition in Indonesia - Sri Sulystyaningsih Natalia Daeng Tiring; Wendelinus O.Janggo (AL-ISHLAH: Jurnal Pendidikan, 2025)
Chemistry education in Indonesia often faces challenges such as abstract content, limited laboratory access, and lack of contextual learning. Integrating local wisdom into science instruction offers a culturally relevant approach to enhance student engagement and understanding. This study aimed to develop an interactive e-module on acid–base concepts contextualized through the traditional Poto Wua Ta’a practice in Sikka Regency, Indonesia. Using the 4D development model (Define, Design, Develop, Disseminate), the module was created by integrating acid–base theory with cultural practices involving betel leaf, areca nut, and lime. Expert validation involved five validators assessing the content, media, and language components. Feasibility was tested through individual (n=10), small-group (n=30), and field trials (n=60), with both qualitative and quantitative data collected. Expert validation yielded an average Aiken’s V score of 0.89, indicating high content validity. Practicality scores increased across trials: 87% (individual), 89% (small group), and 91% (field), all categorized as "very practical." Student feedback confirmed improved understanding of acid–base concepts through cultural context and multimedia features. The e-module effectively contextualizes abstract chemistry content using local wisdom, enhancing student comprehension and motivation. Its development aligns with constructivist, ethnopedagogical, and place-based learning principles, while supporting goals in the Merdeka Curriculum and SDG 4.